A descriptive analysis on the gendered distribution of labour and participation in household economic activities in Manipur, India - Sharma, Meghajit (University of Agricultural Sciences, Bangalore, 2019)
Presented by Meghajit Sharma (UAS/GKVK), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.